If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(w + -6) + 2w = 12 Reorder the terms: 4(-6 + w) + 2w = 12 (-6 * 4 + w * 4) + 2w = 12 (-24 + 4w) + 2w = 12 Combine like terms: 4w + 2w = 6w -24 + 6w = 12 Solving -24 + 6w = 12 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 6w = 12 + 24 Combine like terms: -24 + 24 = 0 0 + 6w = 12 + 24 6w = 12 + 24 Combine like terms: 12 + 24 = 36 6w = 36 Divide each side by '6'. w = 6 Simplifying w = 6
| 3(0)+4b=375 | | 11y-42x+3x-15y= | | h-41=79 | | 12x+14=98 | | -2x+6x=4(x-5) | | 685+85m=23 | | -14-16+6=-12 | | 7x-6(-2x+2)=-183 | | -1-5y=15y-6 | | 5b^2+33b-14=0 | | 8+8t+14q+3t-2q-7= | | -17=7(u+4)+8u | | 41X+23y=4 | | 5x+5x+5x+5x+5x+5x=(x+14)+(x+17)+(8x+9) | | 34-14=78 | | 4=3x+14 | | (x+4)(x-5)=4(x-2) | | 13x-6=-97 | | x-x=128 | | -x^2-6x-8=8 | | lx-7l=2x-10 | | 0.4s=0.7 | | 4.8(x-2)=0.2x+30.4 | | 8x^2+49x+351=0 | | 50x^6-18x^4=0 | | 2x-42=x+11 | | -52+z=92 | | -37-5x=-77 | | -52x+6=10 | | 2x-3=x/2+2 | | 3x(-11x+1)= | | 5a+2b=3a+3b |